Effect of Niobium Dopant on ZnO Thin Films Prepared via the Sol–gel Spin Coating Method - Eswar, Kevin Alvin; Rostan, Nur Fairuz; Mohamad, Maryam; Md Akhir, Rabiatuladawiyah; Rasmidi, Rosfayanti; Guliling, Muliyadi; Azhar, Najwa Ezira; Buniyamin, Irmaizatussyehdany; Malek, Mohd Firdaus; Mahmood, Mohamad Rusop; Suhaimi, Husairi Fadzilah; Abdullah, Saifollah (UI Scholars Hub, 2025)
Thin films of zinc oxide (ZnO) and niobium (Nb)-doped ZnO were deposited on a glass substrate using the sol–gel spin coating method. Diethanolamine, isopropyl alcohol, and zinc acetate served as the stabilizers, solvent, and starting ma-terial, respectively. Niobium pentachloride was employed as the dopant source. Energy-dispersive X-ray analysis con-firmed Nb incorporation. Field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), and ultravio-let–visible spectroscopy (UV–Vis) analyses characterized the morphology, structure, and optics of the films, respective-ly. Both films, comprising nanoparticles, were visible in FESEM. Nb doping reduced the particle size from 44.2 nm to 35.8 nm. The XRD peaks at 31.23°, 33.48°, and 35.7° indicate the (100), (002), and (101) orientations, respectively. Nb-doped ZnO exhibited enhanced visible-range transmission in UV–Vis analysis. However, UV spectrum transmission significantly decreased. Nb doping reduced the optical bandgap of ZnO from 3.30 eV to 3.27 eV.